Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae) - Ahmed, Mohammed; Boström, Sven; Holovachov, Oleksandr (European Journal of Taxonomy, 2020)
This paper reports on the genus Cobbionema Filipjev, 1922 in Sweden with the description of four species and a revision of the genus. Cobbionema acrocerca Filipjev, 1922 is relatively small in size, with a tail that has a conical proximal and a digitate distal section. Cobbionema cylindrolaimoides Schuurmans Stekhoven, 1950 is similar to C. acrocerca in most characters except having a larger body size and heavily cuticularized mandibles. Cobbionema brevispicula sp. nov. is characterised by short spicules and a conoid tail. Cobbionema acuminata sp. nov. is characterised by a long two-part spicule, a conical tail and three (one mid dorsal and two ventrosublateral) sharply pointed tines in the anterior chamber of the stoma that are located more anterior than in all the other species. We also present a molecular phylogeny of the family based on the nearly full-length 18S and the D2-D3 expansion segment of the 28S rRNA genes. Maximum Likelihood and Bayesian trees inferred from both genes strongly support a clade that included Cobbionema, Demonema Cobb, 1894 and Halichoanolaimus de Man, 1888 and another clade with Gammanema Cobb, 1920 and Latronema Wieser, 1954 nested together. None of the trees supported the monophyly of the subfamilies Choniolaiminae and Selachinematinae.